The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/ece3.6914
|View full text |Cite
|
Sign up to set email alerts
|

Projected climate change threatens significant range contraction of Cochemiea halei (Cactaceae), an island endemic, serpentine‐adapted plant species at risk of extinction

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 93 publications
(171 reference statements)
0
2
0
Order By: Relevance
“…(i.e., the five taxa in Cochemiea sensu (K. Brandegee) Walton) is the Cape Region of Baja California, with a jump to the Pacific Coast of the Baja California peninsula at about 3 Ma, and then dispersal back to the Cape Region for C. poselgeri at 2.5 Ma, with the island dispersal of C. halei occurring as recently as 500,000 years ago. In spite of its recent dispersal to the archipelago in Bahía Magdalena, C. halei shows a suite of pronounced morphological differences from its sister taxon, C. poselgeri , as well as a facultative relationship with serpentine, a form of ultramafic ocean crustal rock that forms the bedrock of the island (Breslin et al, 2020 and the references therein). This suggests rapid adaptation to an environment markedly different from both the northern Pacific coast and the Cape Region of Baja California.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(i.e., the five taxa in Cochemiea sensu (K. Brandegee) Walton) is the Cape Region of Baja California, with a jump to the Pacific Coast of the Baja California peninsula at about 3 Ma, and then dispersal back to the Cape Region for C. poselgeri at 2.5 Ma, with the island dispersal of C. halei occurring as recently as 500,000 years ago. In spite of its recent dispersal to the archipelago in Bahía Magdalena, C. halei shows a suite of pronounced morphological differences from its sister taxon, C. poselgeri , as well as a facultative relationship with serpentine, a form of ultramafic ocean crustal rock that forms the bedrock of the island (Breslin et al, 2020 and the references therein). This suggests rapid adaptation to an environment markedly different from both the northern Pacific coast and the Cape Region of Baja California.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the Mammilloid clade in Baja California has perhaps been resilient to the repeated cooling and warming cycles that characterized the Pleistocene. On the other hand, Breslin et al ( 2020 ) found that the island endemic Cochemiea halei is likely to lose 53% of its highly restricted suitable habitat by 2100. Further research is needed to understand the impacts of climate on the Mammilloid clade on different spatial and temporal scales.…”
Section: Discussionmentioning
confidence: 99%